2008
DOI: 10.1002/smll.200700236
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluorescent Silica Nanoparticles: Towards Ultrabright Silica Nanoparticles

Abstract: A new class of silica fluorescent nanoparticles (≈30‐nm diameter; see image) is described, in which organic fluorescent dyes are physically entrapped inside self‐sealed silica nanochannels. The 1D confinement of the dye molecules inside the channels means the dyes can be packed without quenching fluorescence, ≈250 times denser inside the nanoparticles than in aqueous medium. The synthesized particles are compatible with labeling biological cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 25 publications
(31 reference statements)
2
85
0
Order By: Relevance
“…and there has been a subsequent effort to scale it down to the nanoscale, in order to produce UFSNP. [ 29 ] The fl uorescence of the dye inside these particles was not quenched, even though its concentration was ≈ 230 times higher than the maximum nonquenching concentration of free dye in aqueous solution. Nonetheless, these UFSNP were not quite ultrabright.…”
Section: Particle Sizesmentioning
confidence: 98%
See 1 more Smart Citation
“…and there has been a subsequent effort to scale it down to the nanoscale, in order to produce UFSNP. [ 29 ] The fl uorescence of the dye inside these particles was not quenched, even though its concentration was ≈ 230 times higher than the maximum nonquenching concentration of free dye in aqueous solution. Nonetheless, these UFSNP were not quite ultrabright.…”
Section: Particle Sizesmentioning
confidence: 98%
“…Nonetheless, these UFSNP were not quite ultrabright. Compared to a popular class of bright fl uorescent particles (water dispersible quantum dots) [ 30 ] UFSNP have been reported [ 29 ] at ≈ 40% of the quantum dot brightness. This is almost two orders of magnitude lower than that expected from simply geometrically scaling down the previously reported ultrabright micrometer-sized particles, [ 26 , 27 ] which is presumably due to dye leakage from the channels.…”
Section: Particle Sizesmentioning
confidence: 99%
“…The third class of system shown in Fig. 1 is polymerinorganic composites which are characterized by a chemically more complex and often scarcely characterized interface [5,[26][27][28][29]. These materials systems have a variety of advantages which start with the opportunity of self assembly and materials integration into hierarchically organized structures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hybrid structures comprising biopolymers and functional inorganic phases can replace conventional materials in several high technology or bioapplications that are performed in the ambient or under biocompatible conditions. Many nanocomposites are composed of a luminescent organic dye that is attached to or incorporated in the inorganic nanoparticle [5,[26][27][28][29]. Chemical and thermal stability issues as well as materials deterioration via leaching of the luminescence component, however, are continued challenges in the development of this class of material.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that there is a concentration threshold above which the formation of aggregates causes the presence of non-radiative dis-excitation patterns and the decrease of the fluorescence efficiency. To achieve mesoporous nanostructures with large emission efficiency is a goal still open, in particular for applications in photonics, such as solid state dye laser, and in the biomedicine field to achieve fluorescent nanoprobe for cell imaging [10][11][12][13][14][15][29][30][31][32][33][34][35]. In this respect in the last years new synthesis procedures were proposed to solve the exposed drawbacks to achieve ultrabright nanostructures by sealing the matrix by means of a templated procedure, by proper functionalization.…”
Section: Introductionmentioning
confidence: 99%